DOES TECHNOLOGY MATTER IN THE WORLD OF LOYALTY? RESEARCH OF SELF SERVICE TECHNOLOGY AND CUSTOMER LOYALTY (CASE STUDY : BURGER KING MANADO) - Vitto Jarzal Zendling Machmoed; Stanss L. H. V. Joyce Lapian; Emilia M. Gunawan (Universitas Sam Ratulangi, 2022)
At present, the impact of the covid 19 pandemic which has now become a covid 19 endemic has an impact on changing consumer behavior in everyday life. Burger King Manado has improvised and improved its service aspect by launching self-service technology to replace facing this problem. By providing features that can make it easier for customers, there are also various attractive promos for loyal customers of Burger King Manado. To find the effect of self-service technology that has been carried out by Burger King Manado, this study proposes and examines the effect of self-service technology on customer loyalty with customer satisfaction as a mediating variable. The goal is based on the assumption that improvements made with self-service technology will affect satisfaction and loyalty to Burger King Manado who have used the technology. This study used 100 samples and used the purposive sampling method. The method of data collection was done by distributing online questionnaires. The data analysis technique used in this research is path analysis. The results of this study indicate that self-service technology quality has a positive and significant impact on customer loyalty and customer satisfaction is proven to be a mediating variable. These results provide insight for other companies to invest in new technologies to improve customer experience, satisfaction, and loyalty. Keyword: self-service technology, customer loyalty, customer satisfaction